Development of 3D sketching in cave virtual reality environment towards the development of competent building professional graduates. - Rahimian, Farzad Pour; Ibrahim, Rahinah (2007)
Electronic Design Automation (EDA) and Computer-Aided Architectural Design (CAAD) tools do not typically support collaborative work. This problem is magnified further when designers are geographically dispersed and with different time zones. The EDA and CAAD design semantic will become more difficult to capture and reuse from one design team to another. In this paper, we would like to study the use of Cave Automatic Virtual Environment (CAVE)-a Virtual Reality (VR) platform-in order to develop a new generation of architects who will be working in geographically dispersed locations. The VR technology we utilize will have a real-time manipulation capability and can be used collaboratively for exploring alternative design options and simulating different stages of the . building design process. This paper would like to illustrate how 3D sketching could be developed as a medium in the CAVE collaborative design education environment. It will 1) identify issues and challenges for multidisciplinary and geographically distributed architecture!engineering! construction in project collaborations; 2) describe some aspects of the conceptual design process; 3) describe the background literature of the proposed 3D sketching in VR as a new tool and compare it with traditional methods of design; and 4) recommend how 3D sketching could be developed as a collaborative medium in a VR environment. The results of this paper can become a stepping-stone for future development of cutting-edge information technologies. Additionally, the educational programs using this methodology will develop professional graduates who are competent in multi-disciplinary teamwork and equally competent in utilizing ITIICT in delivering their bUilding projects within time and budget.